Effects of Boron Phosphate Additive on Ceramics with Anorthite Phase - Meltem ÇUBUK; Metin GÜRÜ; Bülent BARAN; Ali Sacid AĞIR (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
In this study, the anorthite phase was chosen as a ceramic type that can withstand thermal shock. First, boron phosphate was synthesised, boron phosphate was calcined at 1000°C and characterized by XRD and chemical analyzes. On the other hand, in the phase diagram, the most suitable eutectic points covering the anorthite phase (CaO, Al2O3 , SiO2) and at the lowest temperature at which anorthite can form are selected. 6 mixtures were prepared using wollastonite, kaolinite and calcite. The 6 mixtures prepared were separated into two equal parts and the second parts were added of BPO4 10%. The mixtures were pressed at the same pressure and cooked under the same conditions and at the same heating rate in the electric oven at 1050, 1100, 1150 and 1200°C. DTA and TGA analyzes were applied to the samples before sintering, and XRD analyzes were applied to the sintered samples. According to the test results, the addition of the synthesized BPO4 has shown that the anorthite phases are formed at temperatures well below the theoretical formation temperatures without swelling.